Bortezomib Does Not Prevent the Occurrence of Kaposi's Sarcoma in Patients with Haematological Malignancies: Two Case Reports - Nathalie Chavarot; Celeste Lebbe; Eric Thervet; Didier Bouscary; Alexandre Karras (Medical Journals Sweden, 2017)
Abstract is missing (Short communication)